Benzotriazole decorated graphene oxide for efficient removal of U(VI). (October 2019) - Ding, Jie; Yan, Zijun; Feng, Lanqi; Zhai, Fuwan; Chen, Xiao; Xu, Yuwei; Tang, Siqun; Huang, Chao; Li, Laicai; Pan, Ning; He, Yi; Jin, Yongdong; et al.
Abstract: There is a need to develop highly efficient materials for capturing uranium from nuclear wastewater. Here, 5-methylbenzotriazole modified graphene oxide (MBTA-GO) was used to adsorb U(VI) from aqueous solution. By the trials of different conditions, we found that the removal of U(VI) from acidic solution was strongly dependent on pH but independent of ionic strength. The U(VI) adsorption was perfectly conformed to the pseudo-second-order kinetics and the adsorption isotherms were simulated by the Langmuir model well. A high removal capacity ( q max  = 264 mg/g) for U(VI) at pH 3.5 was obtained. XPS, EXAFS analyses and DFT calculations revealed that the mechanism of uranium capture was ascribed to (i) the surface complexation by benzotriazole and carboxyl groups (providing lone pair electrons) on MBTA-GO and (ii) enhanced synergistic coordination ability of delocalized π-bond of triazole group toward U due to the transfer of electrons from graphene sheet to benzotriazole. DFT calculations further demonstrated that benzotriazole displayed stronger binding with U(VI) compared to carboxyl group due to higher binding energy of [Side/Surface-U-MBTA-GO] (79.745, 54.986 kcal/mol) than [MBTA-GO–COOH–U] (27.131 kcal/mol). This work will provide valuable insight into designing novel nitrogen-containing adsorbents for practical application in wastewater treatment. Graphical abstract: Image 1 Highlights: 5-methylbenzotriazole modified GO (MBTA-GO) presented excellent adsorption capacity for U(VI). XPS and EXAFS spectra revealed the interaction mechanism was surface complexation. DFT calculations demonstrated the delocalized π-bond of triazole group could enhance uranium capture of MBTA-GO. The transfer of electrons from graphene sheet to benzotriazole strengthened coordination ability of delocalized π-bond. Abstract : Capsule: The role of benzotriazole for improving the adsorption performance and operation of GO is elucidated for the first time.